Malaysian automobile industry and green supply chain management - Rafia, Afroz; Rahman, Mohammed Ataur; Muhib, Md. Muhibbullah; Morshed, Niaz (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The automotive industry is one of the main producers of industrial wastes affecting the natural environment. The purpose of this study is to identify the most important barriers to the Malaysian automotive industry. Researching 145 companies in Malaysia’s automotive supply chain industry collected the data. The data were examined using Problem Conflict Index (PCI) to determine the most important critical barriers that put automotive companies in a difficult position to implement green supply chain management (GSCM). The results of this study report that the number one barrier in the automotive sector is "market competition and uncertainty" with a PCI of 298. The second problem is “Lack of Implementing Green Practice” with the PCI of 297. Like these two barriers, cost implications, unawareness of customers, lack of corporate social responsibility, lack of globalization, lack of technical assistance from the government have been identified as top-level barriers and lack of the government’s willingness to invest, reduced involvement in environmentally related conferences. The elimination of these barriers will help to apply the GSCM in the Malaysia automobile industry.